2020
DOI: 10.1002/slct.202003784
|View full text |Cite
|
Sign up to set email alerts
|

Carboxamides Bearing Sulfonamide Functionality as Potential Novel Phospholipase A2 Inhibitors

Abstract: Phospholipase A2 (PLA2) is a well‐known drug target for the treatment of inflammation‐related diseases. In this study, we reported the synthesis and biological screening of a series of new carboxamides bearing sulfonamide functionality for PLA2 inhibitory potency and 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) free radical scavenging activity. Also, computational technique was employed to characterize the binding poses of top‐ranking derivatives. The biological assay shows that all the compounds inhibited the enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Furthermore, the present findings are consistent with those of El-Sayed et al [ 42 ] and Barakat et al [ 43 ] regarding the inhibition by certain quinazoline and pyrimidine derivatives against sPLA2 and cPLA2. Also, the present findings are consistent with those of Ibezim et al [ 44 ] who reported the inhibitory effect of certain sulfonamide derivatives against 3CLpro, sPLA2, and cPLA2. Our results suggest that the combination of quinazoline and sulfamerazine structural features in a single molecule increased the inhibitory activity against 3CLpro, sPLA2, and cPLA2.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the present findings are consistent with those of El-Sayed et al [ 42 ] and Barakat et al [ 43 ] regarding the inhibition by certain quinazoline and pyrimidine derivatives against sPLA2 and cPLA2. Also, the present findings are consistent with those of Ibezim et al [ 44 ] who reported the inhibitory effect of certain sulfonamide derivatives against 3CLpro, sPLA2, and cPLA2. Our results suggest that the combination of quinazoline and sulfamerazine structural features in a single molecule increased the inhibitory activity against 3CLpro, sPLA2, and cPLA2.…”
Section: Discussionsupporting
confidence: 93%
“…The coordinate of P. falciparum falcipain-2 (FP2) along with its cocrystallized inhibitor (E64) were retrieved from the protein databank (pdb code 3BPF) [ 22 ] and the complex was prepared for molecular simulation purposes following standard procedures described [ 23 , 24 ]. Water and non-essential small molecules were deleted and hydrogen atoms were added to the FP2-E64 complex with Protonate 3D Wizard of Molecular Operating Environment (MOE) (Molecular Operating Environment, version 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The cocrystallized water molecules and other non-essential particles were removed to retain only the protein-ligand complex. The Protonate 3D procedure implemented in molecular operating environment (MOE) software was used to protonate the complex before energy minimizing it to gradient of 0.001 kcal/mol using the Merck Molecular (MMFF94) force field to eliminate atomic clashes 21 , 22 , 23 .…”
Section: Methodsmentioning
confidence: 99%